A reconstructive algorithm of oncologic defects of the upper trunk and shoulder girdle: Factors predicting complexity and outcomes. Issue 2 (3rd May 2020) - Nemir, Stephanie; Mericli, Alexander F.; Adelman, David M.; Liu, Jun; Feig, Barry W.; Lin, Patrick P.; Roubaud, Margaret S.
Abstract: Background: Locally advanced malignancies of the upper torso and shoulder girdle (UT‐SG) necessitate extensive resection and complex reconstruction. Due to the infrequent nature of these operations, a global reconstructive algorithm has not been defined. Methods: A retrospective review of all patients who received reconstructive surgery following malignant tumor extirpation in the UT‐SG from 2008 to 2018 at the University of Texas MD Anderson Cancer Center. Factors predicting the need for flap reconstruction and risk for postoperative complications were evaluated. Results: In total, 252 procedures met inclusion criteria. The most common pathology was sarcoma (76%) and 52% were primary tumors. The median defect area was 112 cm 2 (range 4‐1350 cm 2 ). Reconstructive techniques included pedicled flaps (46%), local tissue rearrangement (38%), and free flaps (16%). On univariate analysis, the probability of needing a free flap increased 39% when the defect size increased by 100 cm 2 . The strongest independent predictors of requiring a free flap were major vessel exposure (adjusted odds ratio [OR] = 4.92, 95% confidence interval [CI], 1.36‐17.84, P = .015) and major peripheral nerve exposure (adjusted OR = 3.2, 95% CI, 1.1‐9.2, P = .031). Conclusion: Despite the aggressive nature of their malignancies, patients requiring an UT‐SG resection demonstrate high survival rates and therefore demand a durable reconstruction. Exposed critical structures and defect size were predictive of free tissue transfer.